2019
DOI: 10.1093/cercor/bhz078
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine Receptor Expression Among Local and Visual Cortex-Projecting Frontal Eye Field Neurons

Abstract: Dopaminergic modulation of prefrontal cortex plays an important role in numerous cognitive processes, including attention. The frontal eye field (FEF) is modulated by dopamine and has an established role in visual attention, yet the underlying circuitry upon which dopamine acts is not known. We compared the expression of D1 and D2 dopamine receptors (D1Rs and D2Rs) across different classes of FEF neurons, including those projecting to dorsal or ventral extrastriate cortex. First, we found that both D1Rs and D2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 99 publications
4
28
0
Order By: Relevance
“…We studied the pattern of adrenergic receptor expression across different layers and different classes of neurons in the FEF. Since evidence points to coexpression and cooperativity of dopamine receptors and adrenergic receptors in the PFC (Montezinho et al, 2006;Mitrano et al, 2014), we hypothesize that α1 and β1 adrenergic receptors might be expressed more heavily on long-range projecting pyramidal neurons, whereas α2 and β2 adrenergic receptors might be expressed more heavily on GABAergic interneurons, similar to patterns of dopamine expression in the FEF that have been found in previous studies (Mueller et al, 2018(Mueller et al, , 2020.…”
Section: Introductionsupporting
confidence: 69%
See 3 more Smart Citations
“…We studied the pattern of adrenergic receptor expression across different layers and different classes of neurons in the FEF. Since evidence points to coexpression and cooperativity of dopamine receptors and adrenergic receptors in the PFC (Montezinho et al, 2006;Mitrano et al, 2014), we hypothesize that α1 and β1 adrenergic receptors might be expressed more heavily on long-range projecting pyramidal neurons, whereas α2 and β2 adrenergic receptors might be expressed more heavily on GABAergic interneurons, similar to patterns of dopamine expression in the FEF that have been found in previous studies (Mueller et al, 2018(Mueller et al, , 2020.…”
Section: Introductionsupporting
confidence: 69%
“…than either neurogranin+ or RP+ general pyramidal neuron classes across all four adrenergic receptor subtypes. The disproportionately high rate of adrenergic receptor expression among long-range projecting pyramidal neurons mirrors what was found for dopamine receptors in macaque FEF (Mueller et al, 2018(Mueller et al, , 2020. However, unlike dopamine receptors, which had higher rates of expression of D1Rs compared to D2Rs (Mueller et al, 2020), all four adrenergic receptor subtypes are expressed in very similar proportions on longrange pyramidal neurons.…”
Section: Adrenergic Receptors Are Disproportionately Expressed On Lonsupporting
confidence: 64%
See 2 more Smart Citations
“…In our large-scale model, VIP/CR cells selectively disinhibited the dendrites of cells selective to the target stimulus, allowing target-related activity to flow through the cortical network. D1 receptors in monkey cortex are more strongly expressed on SST/CB neurons than other interneuron types (Mueller et al 2019), and application of dopamine to a frontal cortex slice increases inhibition to the dendrite, and decreases inhibition to the soma of pyramidal cells (Gao et al 2003). We found that, as long as local cortical areas (or potentially cortico-subcortical loops) are capable of maintaining persistent activity, then shifting the balance of inhibition from the soma to the dendrite can allow for maintenance of an active representation of a stimulus in persistent activity, while shielding it from distracting input from sensory areas.…”
Section: Dopamine Increases Distractor Resistance By Shifting the Submentioning
confidence: 97%